(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The objective to be achieved in this study is to determine the extent of the influence of corporate governance on banking performance in the aftermath of the global financial crisis in 2008. The secondary data type is in the form of corporate financial statements. In measuring company performance, researchers used return of equity data that started from 2010 to 2019. Then, in measuring corporate governance, we focused on three aspects in the structure of the board of directors, the structure of the board of commissioners, and the structure of company ownership. The first aspect consists of the size of the board of directors. The second aspect consists of the size of the board of commissioners and board independence. The third is ownership by institutions (institutional ownership) and large ownership (large shareholders). The results showed that of the three aspects of corporate governance, the only variable that has a significant impact toward return on equity is large shareholders.